“Diritto” e “religione” nell’Australia indigena (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Il diritto Yolngu come “credenza religiosa” - 2. Tre xenonimi Yolngu dell’italiano ‘diritto’ - 2.1. ‘Rom’ - 2.2. ‘Madayin’ - 2.3. ‘Ngarra’ - 3. La “connessione” tra “diritto” e “religione” Yolngu: likan - 4. “Diritto” e “religione” Yolngu: una duplice correlazione.“Law” and “religion” in Indigenous AustraliaABSTRACT: This work takes on the relationship between law and religion in Indigenous Australian societies, particularly focusing on Yolngu group (North-East Arnham Land). The essay aims to enlighten the nature of the “connection” between “legal” and “sacred” dimensions of Yolngu culture and cosmology, originally noted in several Australian judicial decisions and governamental reports. First, the essay undertakes a linguistic analysis of Yolngu terminology surrounding law, presenting three Yolngu terms translatable as “law” and discussing their meaning and bond with Yolngu sacred ancestors and ritual objects and ceremonies. Second, it explains the essence of the connection between law, sacred ancestors and ritual objects and ceremonies by presenting the Yolngu linguistic and conceptual category of “likan”. The article concludes that Yolngu law is a “sacred” one in at least a two-fold way: beacuse it was surrendered to humans by sacred ancestors; and since it arises from ritual objects and ceremonies.